Artificial evolution : 8th international conference, Evolution Artificielle, EA 2007 : Tours, France, October 29-31, 2007 : revised selected papers /: 8th international conference, Evolution Artificielle, EA 2007 : Tours, France, October 29-31, 2007 : revised selected papers. (2020) - Unknown
No abstract available